On the EPA's Radar: The Role of Financial Reports in Environmental Regulatory Oversight - LI, BIN; WANG, ANNIKA YU (Journal of Accounting Research, 2024)
ABSTRACT This paper investigates the role of corporate financial reports in the Environmental Protection Agency's (EPA) regulatory activities. By tracking the EPA's direct retrieval of SEC filings, we identify three key findings. First, the EPA retrieves a large volume of financial reports, especially from firms in high‐pollution industries. Second, the EPA is more likely to access financial reports during enforcement investigations and significant rule proposals, but less so during compliance monitoring, with patterns varying predictably across firms. Third, the EPA's reliance on financial reports is potentially driven by its demand for information on firm liquidity, solvency, and profitability. Overall, our study highlights the usefulness of financial reports for the EPA as an environmental regulator.